2019
DOI: 10.1007/s12325-019-01112-3
|View full text |Cite|
|
Sign up to set email alerts
|

Co-Creation of a Lanreotide Autogel/Depot Syringe for the Treatment of Acromegaly and Neuroendocrine Tumours Through Collaborative Human Factor Studies

Abstract: IntroductionAlthough the previous lanreotide autogel/depot syringe had been well received, feedback indicated that improvements could be made to make it more user-friendly. Additionally, the view that patients should have greater involvement in the research and development process is echoed by the International Neuroendocrine Cancer Alliance. A series of studies aimed to develop and validate a new syringe that works better for patients, caregivers and healthcare professionals (HCPs) by involving these groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
1
16
0
1
Order By: Relevance
“…In a previous preference study published in 2012, nurses preferred the lanreotide autogel/depot (LAN) syringe compared with that of previous octreotide long-acting release (LAR) [7,8]. Although nurses preferred the LAN syringe overall and for nearly all syringe attributes, the sturdiness of the plunger received a higher rating for the octreotide LAR syringe [7]; this is consistent with feedback from patients, caregivers and healthcare professionals obtained during a series of formative interviewbased studies [9].…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…In a previous preference study published in 2012, nurses preferred the lanreotide autogel/depot (LAN) syringe compared with that of previous octreotide long-acting release (LAR) [7,8]. Although nurses preferred the LAN syringe overall and for nearly all syringe attributes, the sturdiness of the plunger received a higher rating for the octreotide LAR syringe [7]; this is consistent with feedback from patients, caregivers and healthcare professionals obtained during a series of formative interviewbased studies [9].…”
Section: Introductionsupporting
confidence: 67%
“…In a previous study, the overall preference score by nurse assessment was 63 percentage-points higher for the LAN previous syringe compared with the previous octreotide LAR syringe [7] and, in another study, 81% of patients who switched from octreotide LAR to LAN preferred to continue treatment with LAN [16]. Given the almost universal preference for the LAN new syringe in the PRESTO study, this suggests that the advancements made for the LAN syringe (larger flanges; a larger, more rigid non-transparent needle cap; new plunger supports; new protective tray) [9] following feedback from nurses [7] and from patients, caregivers and nurses in formative human factors studies [9] resulted in improved user experience with this new device.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is interesting to consider that future studies might reveal a shift towards home-based healthcare, especially in the era of the coronavirus disease 2019 (COVID-19) pandemic, and, as such, the option for self- or partner-injection may become a more prominent feature in treatment decision-making. Furthermore, a recent study evaluating patient experience using a LAN syringe introduced in 2019 indicated that use of newer injection devices could further reduce pain and anxiety for patients [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients, patient advocates, and healthcare practitioners (HCPs) believe patients with NETs are not sufficiently involved in research supporting their treatment [ 14 ]. In a series of human factors studies, patients, HCPs, and non-HCP caregivers tested prototype syringes intended to treat acromegaly and NETs, helping to better design a user-centered device [ 15 ]. This suggests there is an opportunity to better inform treatment development with greater patient involvement.…”
Section: Introductionmentioning
confidence: 99%